Burma: Ways out of isolation - Gerhard Will (Stiftung Wissenschaft und Politik (SWP), 2003)
In the early 1990s the EU and the USA responded to the 1988 military coup in Burma and the new government's failure to recognise the opposition's 1990 election victory by publicly condemning the new regime, terminating development co-operation, erecting trade barriers and drastically scaling back political contacts with the country. The prospects of lifting economic sanctions and improving the political situation were made conditional on the following requirements: the opposition had to be given total political freedom of action; the parliament elected in 1990 had to be convened; and a legitimate democratic government had to be formed. (SWP Comments / SWP)
Keywords: 320